Chemical Characterisation of Podzols in Sabah, East Malaysia - Jopony, Marcus; Tan, Ying chiu (1989)
Chemical analyses were carried out on three podzol samples from the Tambunan and Keningau districts in Sabah. The values of pH, Organic carbon content, cation exchange capacity and HCI extractable metals vary distinctly between horizons. Such variation was most significant between horizons E and Bh and except for pH, the values for the above parameters were lowest and highest in horizons E and Bh respectively.